An unusual O2−/F− distribution in the new pyrochlore oxyfluorides: Na2B2O5F2 (B = Nb, Ta). Issue 14 (27th January 2022) - Boivin, Edouard; Pourpoint, Frédérique; Saitzek, Sébastien; Simon, Pardis; Roussel, Pascal; Kabbour, Houria
Abstract : Two new oxyfluorides with a pyrochlore-type structure, Na2 Nb2 O5 F2 and Na2 Ta2 O5 F2, have been obtained, and for which the XRD crystallographic study coupled with 19 F solid state NMR reveals an unusual O/F distribution. Abstract : Two new oxyfluorides with a pyrochlore-type structure, Na2 Nb2 O5 F2 and Na2 Ta2 O5 F2, have been obtained, for which the XRD crystallographic study coupled with 19 F solid state NMR reveals an unusual O/F distribution. Both materials are n-type semiconductors exhibiting photoconductive properties.